2021
DOI: 10.1002/anie.202101328
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent Degrader for Fibroblast Growth Factor Receptor 1/2

Abstract: Aberrant activation of FGFR signaling occurs in many cancers, and ATP‐competitive FGFR inhibitors have received regulatory approval. Despite demonstrating clinical efficacy, these inhibitors exhibit dose‐limiting toxicity, potentially due to a lack of selectivity amongst the FGFR family and are poorly tolerated. Here, we report the discovery and characterization of DGY‐09‐192, a bivalent degrader that couples the pan‐FGFR inhibitor BGJ398 to a CRL2VHL E3 ligase recruiting ligand, which preferentially induces F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Given the sharp turn created by the acetamide of GSK215,a nd the close proximity of the FAK-and VHL-binding portions,i ti sl ikely that longer linkers would produce different ternary complex structures with alternative positioning of the two proteins.L onger linkers can produce flexible ternary complexes which adopt multiple conformations; [30,33] we hypothesise that while 2 can induce strongly cooperative ternary binding, the rigid GSK215 structure is ak ey factor in its more effective degradation of FAK. Ar ecently reported FGFR-VHL PROTACi ncludes as imilar acetylpiperazine linker, [34] suggesting commonalities in their binding mode and the possibility of transferrable SAR between kinase PROTACs.T his work reinforces the importance of thoroughly surveying linker length and rigidity in PROTACd esign, and the effect small modifications can have on cooperativity and DC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Given the sharp turn created by the acetamide of GSK215,a nd the close proximity of the FAK-and VHL-binding portions,i ti sl ikely that longer linkers would produce different ternary complex structures with alternative positioning of the two proteins.L onger linkers can produce flexible ternary complexes which adopt multiple conformations; [30,33] we hypothesise that while 2 can induce strongly cooperative ternary binding, the rigid GSK215 structure is ak ey factor in its more effective degradation of FAK. Ar ecently reported FGFR-VHL PROTACi ncludes as imilar acetylpiperazine linker, [34] suggesting commonalities in their binding mode and the possibility of transferrable SAR between kinase PROTACs.T his work reinforces the importance of thoroughly surveying linker length and rigidity in PROTACd esign, and the effect small modifications can have on cooperativity and DC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, Gray group synthesized several glutarimide-based CRBN-targeting degraders with various linkers based on FGFR inhibitor BGJ398. 82 Through binding affinity tests and protein-degradation experiments, it was found that the PROTACs based on BGJ398 could degrade TEL-FGFR2 in Ba/F3 cells, while the full-length FGFR2 was poorly degraded in Kato III cells. Therefore, they used VHL ligands to replace CRBN and found the degrader 41 ( DGY-09–192 , Fig.…”
Section: Protacs Targeting Cancer-related Targetsmentioning
confidence: 99%
“…Interestingly, the PROTAC mediated the internalization of EGFR and sorted to lysosomal degradation, although the RTKs usually prefer to be internalized into a recycling endosome ( Zou et al, 2019 ). Du et al (2021) recently reported a bivalent degrader DGY-09-192, which coupled pan-FGFR inhibitor BGJ-398 to a CRL2 VHL E3 ligase ( Figure 15 ). Surprisingly, DGY-09-192 preferentially induced FGFR1 and FGFR2 degradation while largely sparing FGFR3 and FGFR4.…”
Section: Other Small Molecule-based Therapeutic Modalitiesmentioning
confidence: 99%